m6A-binding protein IGF2BP1 promotes the malignant phenotypes of lung adenocarcinoma - Wu, Hansheng; Xu, Haijie; Huang, Shujie; Tang, Yong; Tang, Jiming; Zhou, Haiyu; Xie, Liang; Qiao, Guibin (Frontiers in Oncology, 2022)
Background Lung adenocarcinoma (LUAD), the most common type of lung cancer, poses a significant threat to the life of patients. N6-methyladenosine modification is the most abundant epigenetic modification and may play an important role in the lung carcinogenesis. IGF2BP1 is a newly discovered m6A-binding protein, but little is known about its role in LUAD. Methods Data from TCGA, GEO, Kaplan–Meier Plotter, and GEPIA databases were systematically analyzed to access the expression and prognostic value of IGF2BP1 on LUAD. Real-time polymerase chain reaction, Western blot, and immunohistochemistry were performed to detect the mRNA and protein level of IGF2BP1 in LUAD tissues and para-carcinoma tissues. Functional cell experiments, including Cell Counting Kit-8 assay, Transwell invasion assay, wound healing assay, Annexin V-FITC/PI double-staining assay, and TUNEL assay, were used to investigate the functions of IGF2BP1 on LUAD cell proliferation, invasion, migration, and apoptosis, respectively. The top 50 genes that were positively or negatively related to the expression of IGF2BP1 were identified, and pathway enrichment analysis was performed. m6A modification sites within IGF2BP1-related genes were predicted by SRAMP. Result 16 m6A regulators were significantly differentially expressed in LUAD tissues. IGF2BP1 was upregulated in LUAD tissues compared with para-carcinoma tissues. High expression of IGF2PB1 was significantly associated with higher clinical stages and poor prognosis of LUAD patients. Furthermore, our functional experiments indicated that IGF2BP1 facilitated cell proliferation, invasion, and migration and suppressed apoptosis in LUAD. Functional enrichment analysis of IGF2BP1-related genes indicated enrichment in several pathways related to oncogenesis. Additionally, m6A modification sites were detected within IGF2BP1-related genes. Conclusions Our findings demonstrate that IGF2BP1 plays a contributory role in the development and progression of LUAD. IGF2BP1 has the potential to become a prognostic predictor and therapeutic target for LUAD.